Sex Education and Religion: Edited by Michael J. Reiss & Shaikh Abdul Mabud. Cambridge: The Islamic Academy, 1998, 277 pp. (American Journal of Islam and Society, 2000)
The far-reaching implications of the debate surrounding sex education instate schools are summed up by the late Professor Syed Ali Ashraf in hisForeword to this book: "We are up against a tremendous conspiracy todethrone the religious concept of a human being from the minds of people."Sex education is "just a modus operandi" of the "secularist philosophy" underpinningthis conspiracy (p. 3).1n presenting a number of essays on sex education from different faith andnonfaith perspectives, the editors have succeeded in introducing readers notonly to Islamic concepts of sexual relationships and sex education, but also tothe ideological battle that is being played out with children's education. At thevery heart of this debate we find unanswered and unanswerable questions about liberal democracy and how liberal it can be in allowing minorities toflourish in its midst.The argument basically revolves around the liberal push for increasing individualrights and to see how far such rights can go in relation to responsibilities.As Carole Ulanowsky notes in her contribution titled "Sex Education:Beyond Information to Values," the balance has tipped in favor of rights - aposition that is (perhaps) suitable for the mature educator but which "can leaveyoung people morally adrift" (p. 22).In his overview titled "Values and Sex Education in a Multicultural Society,"Mark Halstead demonstrates that this issue is complex and laced with difficulties;however, "the promotion of 'responsible sexual behavior' has become adominant motif in contemporary sex education in Britain as in other westerncountries" (p. 236). But who is to decide what is "reasonable"? Parents?Educators? Or that thorn in the side of liberal sex educators: religion?In stating Islamic positions on this subject, Noibi and Abdul Mabud coverground that has been well-presented elsewhere; however, the fact that theircontributions are neither out of place nor dated illustrates how little educatorshave learnt from earlier publications by Muslims on this subject. An alternative,less charitable view might conclude that the liberal sex education lobbyhas learnt too much about the Islamic position and has, as a result, strengthenedefforts to undermine it.For example, Michael Reiss proposes that "the way forward may be for societyto make it easier for homosexuals to live in lasting and mutually faithfulsexual relationships" (p. 146), and David Carr asks, "How could any civilizedperson see it as other than a moral advance over bygone tyrannies that homosexualmen and women are no longer persecuted?" (p. 170). Going further,Carr says that "liberal modernity has at least freed us from a range of irrationalprohibitions." This stand taken by both men demonstrates how "liberal values"can in fact be imposed on young people and, in doing so, force them to altertheir own beliefs (and possibly practices). Carr's implication is that the prohibitionof homosexuality in scriptures is "irrational," thereby making his ownstatement "rational." But on what grounds can he make such a judgment? As anumber of contributions remind us, education is not value-free, and it is a mythto suggest that the liberal view of sex education is either neutral or morallysuperior to other views. Abdul Mabud puts it succinctly: "Passivity [and] neutrality"in sex education are themselves "values" (p. 110) ...